NURSING STUDENTS’ BARRIERS IN CARING FOR SCHIZOPHRENIA PATIENTS WITH VIOLENCE RISK - Erna Erawati (Belitung Nursing Journal, 2016)
Background: There is a general consensus that schizophrenia patients have a greater risk to become violent. Caring for schizophrenia patients with risk of violence presents difficult clinical challenges, and it complicates the efforts of nursing student. Analysis of nursing student' barriers may lead to improve nursing management of risk of violence. Objective: The aim of this study is to explore the nursing student barriers in for caring schizophrenia patients with violence risk. Method: A total sample of 22 nursing students completed their experience through reflective diary during clinical placements. The qualitative data were explored by thematic content analysis method using NVivo. Results: Three themes were emerged from the data included: emotions, personal experience, and inadequate communication skills. Conclusion: These themes reflected the barrier of the nursing students when they applied nursing care toward schizophrenia patient with violence risk. Knowing the barriers is very important for successful violence risk management for nursing student.